Visual Analysis of ISIS Discourse Strategies and Types in Dabiq and Rumiyah Online Magazines. Issue 2 (3rd April 2019) - Abdelrahim, Yasser Abuelmakarem A.
Abstract : Dabiq and Rumiyah are two professional online magazines that the Islamic State in Iraq and Sham (ISIS) established between June 2014 and September 2017 to support its broadcasting media. This study examines the visual discourse strategies used in Dabiq and Rumiyah and the association between the discourse types and the visual resources in the two magazines. The study finds that Dabiq and Rumiyah communicate ISIS's messages through five common visual strategies: legitimation, false dilemma, obligation, derogation, and persuasion. Distinctively, Dabiq augmented ISIS discourse, while Rumiyah strove to reassure ISIS's imagined community of ISIS victories. The study concludes that while the discourse of both magazines is mostly descriptive, Rumiyah evoked instructional discourse to educate readers on lone-wolf terror techniques.